WAYS AND PRINCIPLES OF FORMING SPEAKING CULTURE OF STUDENTS IN PRIMARY EDUCATION SYSTEM - Anarbekova Gulzhan Azizbekovna (Galaxy International Interdisciplinary Research Journal, 2022)
This article deals with the psycholinguistic and educational foundations of speech development, the means of implementing the speech development program in educational institutions, the means and methods of speech development of primary school students.